2021
DOI: 10.1038/s41598-021-84041-y
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of cystic fibrosis exacerbation response phenotypes reveals contrasting serum and sputum iron trends

Abstract: The cystic fibrosis (CF) community seeks to explain heterogeneous outcomes of pulmonary exacerbation (PEX) treatment. Serum and sputum inflammatory mediators may identify people with CF (PwCF) at risk for suboptimal responses. However, lack of an established association between response phenotypes and these mediators limits clinical application. In this pilot study, we prospectively characterized treatment response phenotypes by assessing health-related quality-of-life (HRQoL) during PEX. We also measured lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“… 24 As predicted, we observed that TseT had no impact on competition in an iron-deficient host environment. However, with the addition of iron at a concentration comparable with what is observed during viral co-infection and pulmonary exacerbations in CF, 17 , 32 , 33 competition with E. coli was significantly increased ( Figure 4A ). This increase in competition was due to the expression of TseT, as strains unable to secrete TseT performed significantly worse in competition in the host environment ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“… 24 As predicted, we observed that TseT had no impact on competition in an iron-deficient host environment. However, with the addition of iron at a concentration comparable with what is observed during viral co-infection and pulmonary exacerbations in CF, 17 , 32 , 33 competition with E. coli was significantly increased ( Figure 4A ). This increase in competition was due to the expression of TseT, as strains unable to secrete TseT performed significantly worse in competition in the host environment ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 59%
“…Iron is a particularly important signal in the CF respiratory tract, as iron concentrations in the airway are increased not only during viral infection but also during pulmonary exacerbations. 32 , 33 As such, P. aeruginosa likely senses changes in iron bioavailability in the airway and responds to these signals by increasing the expression of the TseT effector.…”
Section: Resultsmentioning
confidence: 99%
“…Classification of CF patients in two groups as sustained symptom-responders (SRs) or non-sustained symptom-responders (NSRs) to treatment for a PEX allowed for the study of serum and sputum iron as a biomarker for this response difference [280]. SRs and NSRs had no significant differences in lung function at pulmonary exacerbation onset and treatment durations.…”
Section: Cystic Fibrosis (Table 2)mentioning
confidence: 99%